A Frame Work for Parallel String Matching- A Computational Approach with Omega Model (Global Journal of Computer Science and Technology, 2013)
Now a day2019;s parallel string matching problem is attracted by so many researchers because of the importance in information retrieval systems. While it is very easily stated and many of the simple algorithms perform very well in practice, numerous works have been published on the subject and research is still very active. In this paper we propose a omega parallel computing model for parallel string matching. Experimental results show that, on a multi-processor system, the omega model implementation of the proposed parallel string matching algorithm can reduce string matching time by more than 40%.
Keywords: string matching; parallel string matching; computing model; omega model